2023
DOI: 10.1302/0301-620x.105b10.bjj-2023-0881.r1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament injuries in female athletes

Fabio Mancino,
Ayman Gabr,
Ricci Plastow
et al.

Abstract: The anterior cruciate ligament (ACL) is frequently injured in elite athletes, with females up to eight times more likely to suffer an ACL tear than males. Biomechanical and hormonal factors have been thoroughly investigated; however, there remain unknown factors that need investigation. The mechanism of injury differs between males and females, and anatomical differences contribute significantly to the increased risk in females. Hormonal factors, both endogenous and exogenous, play a role in ACL laxity and may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Although the literature describes female sex as a risk factor for ACL injury [38,44], it appears not to affect the outcomes after reconstructive surgery [25,51].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature describes female sex as a risk factor for ACL injury [38,44], it appears not to affect the outcomes after reconstructive surgery [25,51].…”
Section: Discussionmentioning
confidence: 99%
“…Tibial eminence had a potential role in inhibiting tibiofemoral translations when a compressive load was transmitted from the distal femur to the tibial plateau. Anterior translation, internal rotation and medial displacement of the tibia relative to the femur, either considered in isolation or in combination, have been proposed as mechanisms involved in ACL strain and injury [7, 12,18]. Previous studies demonstrated that a smaller tibial spine area, a decreased medial tibial spine volume and a narrower eminence width provided less restraint to tibial translation and rotation relative to the femur, thereby increasing the risk of ACL injury [11,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a noticeable concavity exists in the lateral tibial spine, and the depth of this concavity in the sagittal plane might serve as a risk factor associated with ACL injuries. Moreover, it is noteworthy that sex, particularly female sex, has been identified as an independent risk factor for ACL injury [18]. However, discrepancies exist regarding whether specific geometric knee measurements are associated with ACL rupture risk among males and females [3,17,23,31].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, 6% of primary ACLR patients had an associated LET surgery. This may reflect the growing evidence for the role of additional LET procedures in improving rotation stability and reducing the risk of Rezansoff ACL graft failure in high-risk patients [17][18][19][20][21][22][23].…”
Section: Vte Risk Groupsmentioning
confidence: 99%